Sociodemographic and reproductive risk factors in cervical cancer - Kaur, Tajinder; Garg, Shaveta; Mor, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical cancer is the leading cause of cancer deaths in women. In India, cervical cancer is the most common cancer in women followed by breast cancer. A numbers of risk factors reproductive as well as sociodemographic have been widely studied for cervical cancer. The countries where universal screening is restricted because of various reasons economical, lack of resources etcetera, a modified screening procedure which is targeted on the high risk population can help solve the problem. Methods: This prospective study was conducted in a tertiary institute on sexually active women attending the gynaec OPD. A total of 200 women eligible for the study underwent a cytological evaluation and those with positive findings on Pap smear were followed by colposcopy directed biopsy. A detailed proforma including risk factors was filled for each patient and at the end of study data collected was tabulated in a master chart and was analyzed statistically. Results: A total of 200 women underwent screening with Pap smear in present study. The Pap smear was normal in 93 (46.5%) of cases, 77 (38.5%) showed inflammatory smear and 3 (1.5%) subjects had an unsatisfactory smear. The Pap smear was abnormal in 27 (23.5%) of cases constituting 17 (8.5%) cases of LSIL, 2 (1%) of HSIL and 8 (4%) cases of AGS. All the women with LSIL and HSIL were subjected to colposcopy directed biopsy. Amongst 17 cases of LSIL on pap 8 came out as LSIL, 2 were HSIL and rest 7 were inflammatory after histopathological analysis. The 2 cases of HSIL on pap were confirmed as carcinoma in situ after biopsy. The maximum incidence of SIL of 16.66% was observed in age group of more than 40 years. The majority of cases of SIL, 12 (63.2%) had coitus before the age of 18 years. A positive correlation of SIL was seen with decreasing socioeconomic status, 8 (42.1%) of cases of SIL belonged to the low socioeconomic status while this group constituted only 23% of the total subjects. Conclusions: The frequency of malignant and premalignant lesions was found to be significant, further emphasizing the importance of screening of cervical cancer. The prevalence of carcinoma cervix increases with age, in those with young age at first coitus, lower socioeconomic status and with low education level. A modified screening method can be an effective strategy to control cervical cancer in a developing country like India, where cost and manpower is an issue.